Forces acting on the hand during swimming and their relationships to muscular, spatial and temporal factors - Dupuis, R.; Adrian, M.; Yoneda, Y.; Jack, M. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Because of the complex nature of fluid mechanics, research in swimming has not advanced as rapidly as it has in land sports. In particular there is a lack of information concerning measurement of the propulsive forces produced by a swimmer and the resistive forces that impede forward motion during the different phases of a stroke. As early as 1933, Karpovich (1933) identified the resistance encountered by a body being towed through the water. Only recently has the effect of body position on the resistance been investigated (Kent and Atha, 1971; Van Manen and Rijken, 1975). The relationship ofBernoulli's principle to human propulsion in the water was described by Brown and Counsilman (1971). They asserted that both hydrodynamic lift and drag are components of the total propulsive force. Barthels (1975) and Barthels and Adrian (1975) demonstrated the existence of these lift and drag propulsive forces in the butterfly arm stroke but could not quantify such forces. Several recent investigations have focused on the forces that act on the hand during swimming. These have been preliminary investigations of the front crawl stroke with minimal interpretation (Belokovsky, 1971; V an Manen and Rijken, 1975; Boicev and Tzvetkox, 1975). The purpose of this investigation was to examine the muscular forces and the forces acting upon the hand with respect to the kinematics of swimming the back crawl stroke and breaststroke.